Kinetics of densification and grain growth in ultrafine WC-Co composites. (September 2016) - Oliver, C.J.R. González; Álvarez, E.A.; García, J.L.
Abstract: Dilatometer densification measurements were performed on WC-Co composites containing 2, 5 and 10 wt% Co. The runs were carried out under a flow of 10% H2 -Ar up to 800 °C followed by vacuum up to 1400 °C. Analysis of diffusional densification kinetics suggest an initial solid state densification from 800 to about 1190 °C attributed mainly to grain growth-densification indicated by acceptable fittings to a modified Coble intermediate stage model. This behavior was confirmed by grain growth analysis (range 820 to 1400 °C) measured in fractures surfaces of partially densified pellets. It was detected either a softening solid state stage or eventually liquid formation at 1150–1200 °C and a kind of viscous flow densification behavior operating prior to apparently the solution-precipitation liquid phase sintering. The densification model for diffusional liquid phase sintering applied well in the 1260–1400 °C range with 105–150 kcal mole − 1 activation energy depending on Co content. The standard rearrangement stage was also valid partially within the temperature range 1320 to 1400 °C. Certain fittings of present densification data using phenomenological continuous mechanics approach were carried out, obtaining activation energies ranging between 6 and 35 kcal mole − 1 . Although no clear assignments of such values to probable matter diffusion processes could be made, it is noted the latter value (35 kcal mole − 1 ) is close to the 25–36 kcal mole − 1 values obtained for the classical liquid rearrangement stage. Highlights: Grain growth studies, densification data and theoretical analyses of WC-Co with 2, 5 and 10wt% Co Different consolidation mechanisms depending on temperature measured by dilatometry; Δl/lo vs. T(°C) Strong change in Δl/lo between 1130-1230 °C and increased densification for higher cobalt contents Grain growth kinetics analyzed from SEM images and activation energies for grain growth calculated Note: Δl/lo = (l(t, T)-lo)/lo; "l(t, T)" is the linear length (height); "lo" is the initial thickness of the specimen